Alt-Right Gangs: A Hazy Shade of White - Reid, Shannon Elizabeth (University of California Press, 2020)
Alt-Right Gangs provides a timely and necessary discussion of youth-oriented groups within the white power movement. Focusing on how these groups fit into the current research on street gangs, Shannon E. Reid and Matthew Valasik catalog the myths and realities around alt-right gangs and their members; illustrate how they use music, social media, space, and violence; and document the risk factors for joining an alt-right gang, as well as the mechanisms for leaving. By presenting a way to understand the growth, influence, and everyday operations of these groups, Alt-Right Gangs informs students, researchers, law enforcement members, and policy makers on this complex subject. Most significantly, the authors offer an extensively evaluated set of prevention and intervention strategies that can be incorporated into existing anti-gang initiatives. With a clear, coherent point of view, this book offers a contemporary synthesis that will appeal to students and scholars alike.